PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWA PADA PT. MAPPADECENG JAYA LESTARI KOTA PAREPARE - Hartati Hartati (Jurnal Ilmu Manajemen Profitability, 2020)
This research is (1) To find out Racially the environmental conditions here are disciplined and the motivations are affected by kiveda kavawan Rada PT.  Mappadeceng lavalenstari Keta Parenare.  (2) To determine simultaneously the influence of the work environment, work discipline, and work motivation on employee performance at PT Mappadeceng Jaya Lestari, Parepare City, the data collection technique that the researcher used in this research is.  sksevation, questionnaire, documentation and literature study Sebazainopopulation dalom.  In this research, the researchers took a group of employees at PT MaRradecang Java Lestari, which totaled 48 people. As a result of this research,  this research is limited and energy-intensive, so in this study, a sampling technique was used, namely saturated sampling (census).  where seous anota RORulation of small dual education.  Denzau as stated by Sample in this study is 48. Prague.  The results of this study show that (1) the environmental variable (X) has a partial and significant effect on the performance of the employees of PT Marpadecang Jaya Lestari, Kota Paregare with TU 2,505 TA 2,015 and the level of physical acuity kasil data 0.05.  (1,05 (sig = Vaushal work notification X) partially and significantly influence the performance of employees of PT Mappadecang Java Lestari, Parepare City with t of 0.05 (3ig = 0.000 0.05).  (4).  Work environment variable CX), work discipline variable (X) to work performance variable (Y) where F with a probability value of 0.000 which means that in the crater a significant value of 0.05 (5) R zgiare or R squared obtained 0SS means 55 5s penzanub rk environment X), work discipline (X) and metvasikada X) 1 to work performance BY) While the rest of 41.5 a is influenced by other variables not included in this study 4,090 from 2,015 and the level of significance is smaller